2012
DOI: 10.1155/2012/350352
|View full text |Cite
|
Sign up to set email alerts
|

In VivoTesting of MicroRNA-Mediated Gene Knockdown in Zebrafish

Abstract: The zebrafish (Danio rerio) has become an attractive model for human disease modeling as there are a large number of orthologous genes that encode similar proteins to those found in humans. The number of tools available to manipulate the zebrafish genome is limited and many currently used techniques are only effective during early development (such as morpholino-based antisense technology) or it is phenotypically driven and does not offer targeted gene knockdown (such as chemical mutagenesis). The use of RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Next-generation sequencing based RNA-seq analysis has been widely used to uncover expression patterns under different conditions 10 11 . Recently, high-throughput sequencing of small RNA transcriptomes for miRNA discovery and expression profiling has been conducted in numerous model organisms 12 13 and plants 4 14 . Next-generation sequencing technologies have also been used for miRNA studies in a number of non-model organisms including several fish species 15 16 17 18 19 , echinoderms 20 21 22 23 24 , and marine bivalves 7 25 26 27 28 29 .…”
mentioning
confidence: 99%
“…Next-generation sequencing based RNA-seq analysis has been widely used to uncover expression patterns under different conditions 10 11 . Recently, high-throughput sequencing of small RNA transcriptomes for miRNA discovery and expression profiling has been conducted in numerous model organisms 12 13 and plants 4 14 . Next-generation sequencing technologies have also been used for miRNA studies in a number of non-model organisms including several fish species 15 16 17 18 19 , echinoderms 20 21 22 23 24 , and marine bivalves 7 25 26 27 28 29 .…”
mentioning
confidence: 99%
“…For example, it is difficult to design an efficient synthetic miR that targets the ORF, and those that triggered an RNAi response only showed poor knockdown. Interestingly, the literature tends to confirm this phenomenon, not only in zebrafish but also in mouse and rat, but not in C. elegans 789333435. While targeting the ORF in these organisms is difficult for reasons not understood to date, we found that using 3′-UTRs as target led to efficient gene silencing with both our sensor construct and smn1 , supporting the idea that one should prioritize the selection of targets inside the 3′-UTR of the selected gene whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…mmu-miR155 -based plasmid: ‘pcDNA 6.2 GW/EmGFP-miR', containing artificial miRNA-expressing mmu-miR155 backbone, was provided by Dr Donald Love 9 . The eGFP: mmu-miR155 cassette was transferred into pDONR224 using BP clonase reaction (following the manufacturer's instructions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the role of C9orf72 loss-of-function in ALS pathogenesis, our group recently generated a stable zebrafish line with a reduced expression of c9orf72 [ 88 ] using a microRNA-based gene-silencing approach developed for zebrafish [ 89 ]. Unlike MO-based knockdown approach, transgenic zebrafish lines that stably express microRNAs designed to target knockdown desired genes of interest have no apparent non-specific toxic effects [ 90 ]. Reduced c9orf72 function in zebrafish resulted in motor defects, muscle atrophy, motor neuron loss and mortality in early larval and adult stages [ 88 ].…”
Section: C9orf72 Zebrafish Modelsmentioning
confidence: 99%